Influence of the cementing agent and aging in the color of ceramic veneers, ex vivo evaluation - Schmiedl Manzano, Diego Xavier (2020)
Context: Ceramic veneers are shown as an excellent alternative to improve dental aesthetics with ideal optical and mechanical properties. The objective of this study, was to evaluate the influence of the cementing agent and artificial aging on the veneer´s color. Material and Methods: For this, 30 human premolars were carved to receive veneers made with 0.5mm thick porcelain of the same color. The tooth-veneer sets were randomly separated into three groups (n = 10). A first color measurement was performed on each tooth using the Vita Easyshade colorimeter. The cementing process was carried out according to the group, with RelyX ultimate cement, RelyX Veneer and Tetric-N-Flow fluid resin; performing the color measurement. After heat aging treatment, the sets were subjected to a new color evaluation. Results: The data obtained from the measurements, were analyzed by ANOVA with Games - Howell (software SPSS 21), finding less variation between the periods evaluated with the use of RelyX ultimate cement (p = 0.384). Conclusions: Artificial aging caused a color change in all materials evaluated. RelyX Veneer cement and Tetric-N-Flow fluid resin showed greater instability with clinically acceptable color ranges.